Human granulocytic anaplasmosis in Kinmen, an offshore island of Taiwan - Tsai, Kun-Hsien; Chung, Lo-Hsuan; Chien, Chia-Hao; Tung, Yu-Jung; Wei, Hsin-Yi; Yen, Tsai-Ying; Shu, Pei-Yun; Wang, Hsi-Chieh (PLoS neglected tropical diseases, 2019)
Human granulocytic anaplasmosis, a tick-borne infection caused by Anaplasma phagocytophilum, has received scant attention, while scrub typhus, a mite-transmitted disease caused by Orientia tsutsugamushi, is the most common rickettsiosis in Taiwan. The clinical presentations of both diseases are characterized by undifferentiated fever, headache and malaise. Moreover, both pathogens have been detected in small mammals that serve as hosts for chiggers and ticks in the wild. The objective of the present study was to investigate whether human granulocytic anaplasmosis occurs in Taiwan. Blood samples from 274 patients suspected of having scrub typhus in Kinmen, an offshore island of Taiwan, in 2011 and 2012 were retrospectively examined by immunofluorescence assays. IgG antibodies reactive with Anaplasma phagocytophilum was found in 31.8% (87/274) of the patients. Paired serology identified 3 patients with human granulocytic anaplasmosis and 8 patients with coinfection with O. tsutsugamushi and A. phagocytophilum. Laboratory tests showed that elevated serum ALT/AST, creatinine, and BUN levels were observed in patients with anaplasmosis and coinfection, but elevated serum CRP levels, thrombocytopenia, and anemia were only observed in coinfected patients. PCR detected A. phagocytophilum 16S rDNA and p44/msp2 in 2 patients. The phylogenetic analysis suggested that the replicons of the 16S rDNA shared high sequence similarity with the reference sequences in the Korea, USA, Japan, and China. The amplicons of p44/msp2 were close to those of the human variants identified in the USA and Japan. Our findings indicated that A. phagocytophilum infection was prevalent but unrecognized in Taiwan.